2013
DOI: 10.1603/ec12344
|View full text |Cite
|
Sign up to set email alerts
|

Host Egg Age of <I>Leptoglossus occidentalis</I> (Heteroptera, Coreidae) and Parasitism by <I>Gryon pennsylvanicum</I> (Hymenoptera, Platygastridae)

Abstract: Leptoglossus occidentalis Heidemann (Heteroptera, Coreidae) is native to Western North America and is a serious pest for seed production of conifers. The pest was accidentally introduced into Europe in the 1990s. Since then, seed loss has been recorded in Pinus pinea (L.) forests, with a negative impact on the commercial production of pine nuts. Classical biological control of this pest in P. pinea stands is an attractive proposition. Previous work showed that the egg-parasitoid Gryon pennsylvanicum (Ashmead) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…(Hymenoptera: Pteromalidae) (Islam, 1994), Brachymeria lasus (Walker) (Hymenoptera: Chalcididae) (Husni et al, 2001) and Diadromus collaris (Hymenoptera: Ichneumonidae) (Wang & Liu, 2002). Peverieri et al (2013) reported that the development time of the egg parasitoid Gryon pennsylvanicum (Hymenoptera: Platygastridae) is longer in older eggs of Leptoglossus occidentalis Heidemann (Heteroptera, Coreidae), and Da Rocha et al (2006) had the same result for Gryon gallardoi (Brethes) (Hymenoptera: Scelionidae). Crossman (1925) and Kamay (1976) reported that the development time of O. kuvanae was 21 days at 25°C and 14 days at 30°C.…”
Section: Discussionmentioning
confidence: 98%
“…(Hymenoptera: Pteromalidae) (Islam, 1994), Brachymeria lasus (Walker) (Hymenoptera: Chalcididae) (Husni et al, 2001) and Diadromus collaris (Hymenoptera: Ichneumonidae) (Wang & Liu, 2002). Peverieri et al (2013) reported that the development time of the egg parasitoid Gryon pennsylvanicum (Hymenoptera: Platygastridae) is longer in older eggs of Leptoglossus occidentalis Heidemann (Heteroptera, Coreidae), and Da Rocha et al (2006) had the same result for Gryon gallardoi (Brethes) (Hymenoptera: Scelionidae). Crossman (1925) and Kamay (1976) reported that the development time of O. kuvanae was 21 days at 25°C and 14 days at 30°C.…”
Section: Discussionmentioning
confidence: 98%
“…Adequate egg age can improve parasitoid colonization and establishment, resulting in greater pest suppression as reported for Lobesia botrana Denis and Schiffermüller (Lepidoptera: Tortricidae) (Pizzol et al 2012), Leptoglossus occidentalis Heidemann (Heteroptera: Coreidae) (Peverieri et al 2013) and Chilo suppressalis Walker (Lepidoptera: Pyralidae) ). The quality of the nutritive resources decreases with host embryo development.…”
Section: Introductionmentioning
confidence: 90%
“…Leptoglossus occidentalis is another species for which there are biological pest control programs, such as the use of the parasitoid Gryon pennsylvanicum (Ashmead, 1893) (Hymenoptera: Scelionidae) [289]. Yet, laboratory tests have not yielded positive results on the eggs of L. occidentalis [290]. On the contrary, Barta [291] managed to inoculate artificially in the laboratory the fungi M. anisopliae and Isaria fumosoresea (Wize) Brown y Smith, obtaining good results in adults.…”
Section: Biological Controlmentioning
confidence: 99%